Thrombophilia and Pregnancy - Kupferminc, M. J. (Current Pharmaceutical Design, 2005)
Preeclampsia, intrauterine growth restriction and placental abruption greatly contribute to maternal and fetal morbidity and mortality. Thrombophilia is an inherited or acquired condition that predisposes individuals to venous and/or arterial thrombosis. Recently, three important inherited thrombophilias have been discovered. An inherited mutation in the gene coding for coagulation factor V (factor V Leiden), and a mutation in prothrombin that is associated with higher plasma levels of prothrombin. Both mutations result in an increased susceptibility to develop venous thrombosis. Hyperhomocysteinemia, which is associated with mutations in the gene for methylenetetrahydrofolate reductase, is a risk factor for venous and arterial thrombosis. The presence of antiphospholipid antibodies, an acquired thrombophilic condition, is associated with venous and arterial thrombosis. The term placental vasculopathy, is used to describe pathological placental changes that have been associated with preeclampsia, intrauterine growth restriction, placental abruption and fetal loss. The known thrombotic nature of the placental vasculopathy and the increased thrombotic risk with the presence of thrombophilias suggest, a cause-and-effect relationship between inherited and acquired thrombophilias and a number of severe obstetric complications. Testing patients with these complications for thrombophilias may have therapeutic implications for future pregnancies.
Keywords: intrauterine growth restriction